Sistem Monitoring Kelembapan Media Tanam dan Level Air Berbasis ESP32-MQTT - Rizki Misbah Hidayat; Ahmad Agis Fadillah (Switch : Jurnal Sains dan Teknologi Informasi, 2026)
This study discusses the design and testing of a growing media moisture and water level monitoring system based on ESP32-MQTT. The system was developed to support real-time monitoring of growing media conditions and water availability through a monitoring dashboard. This research used an experimental method with a design and implementation approach by developing an ESP32 circuit connected to a capacitive soil moisture sensor and a water level sensor, then sending sensor data to the dashboard through the MQTT protocol and Node-RED. Testing was carried out using a plant pot as the moisture testing medium and a water container as the water level testing medium. The results showed that the growing media moisture sensor displayed 0% in dry and very dry soil conditions, 61% in moist soil, and 89% in very moist soil. The water level sensor displayed 0 cm, 2.4 cm, and 4 cm according to the testing conditions. These results indicate that ESP32-MQTT can be used as an initial prototype for monitoring growing media moisture and water level before being applied to a complete hydroponic or aquaponic system.